2017
DOI: 10.1039/c7ra00810d
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized graphene oxide for anti-VEGF siRNA delivery: preparation, characterization and evaluation in vitro and in vivo

Abstract: GO–PLL–SDGR/VEGF-siRNA inhibits tumor growth as a tumor targeting delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Functionalized GO as a nonviral carrier for siRNA delivery has been explored in previous research. 54 The result of gene therapy is remarkable, but it also has some limitations, such as transfection efficiency, instability etc. In this study, modified GO had the ability to complete co-delivery of DOX and VEGF-siRNA into HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Functionalized GO as a nonviral carrier for siRNA delivery has been explored in previous research. 54 The result of gene therapy is remarkable, but it also has some limitations, such as transfection efficiency, instability etc. In this study, modified GO had the ability to complete co-delivery of DOX and VEGF-siRNA into HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…The abilities for chemical modification in combination with its low cytotoxicity [116] provide GO broad opportunities for biological and medical applications. Late publications report using chemically modified GO as drag carrier for cancer therapy [117] and tool for gene cancer therapy based on ribonucleic acid (RNA) interference [118]. The combination of GO with quantum dots of AgInZnS produces tunable photoluminescence and can be used for in vivo optical imaging of cancer cells and for phototheraphy [119].…”
Section: Medicine and Biologymentioning
confidence: 99%
“…This GO-PLL-SDGR/siRNA complex could deliver VEGF-siRNA into tumor cells and down-regulate the expression of VEGF effectively to inhibit the tumor growth in a S180 xenograft tumor model. 250 These results indicated that targeting cationic GO /siRNA delivery system has great application potential in cancer therapy. Moreover, a GO based siRNA/drug co-delivery system was developed by Zhang et al , which concluded a PEI-grafted GO nanocarrier for delivery of Bcl-2 siRNA and doxorubicin.…”
Section: Non-metallic Core Hybrid With Organic Shell Delivery Systemmentioning
confidence: 92%